Microplastics in African freshwater sediments: A systematic review of characteristics, abundance and analytical methods - David Edem Dinku; Samuel Ndur; Eric Gyimah; Shadrack Fosu; Patience Korley (Cleaner Water, 2025)
Microplastic contamination of freshwater ecosystems is a growing environmental concern due to their persistence and potential to cause ecological risk. This study systematically reviews the abundance and characteristics of microplastics and the analytical techniques used to detect them in African freshwater sediments. Following PRISMA guidelines, 28 studies were reviewed, revealing significant variations in microplastic concentrations across freshwater systems. The results showed a varied microplastic abundance ranging from 0.623 to 27,259 particles/kg, with fibres, fragments, and films being the most frequently reported shapes. White, transparent, green, and blue were the predominant colours observed. The dominant polymer types identified were PE (polyethylene), PP (polypropylene), and PVC (polyvinyl chloride). Sodium chloride was the most commonly used separation solution, while microscopy and Fourier-transform infrared (FTIR) spectroscopy were the primary detection techniques. This review highlights the urgent need for standardised methods to improve comparability among studies and recommends formulating a comprehensive monitoring strategy to guide efforts in reducing microplastic pollution in freshwater ecosystems.